Sustainability assessment of individual-level solar energy poverty alleviation program-A case on Jinzhai County, China - Jin, Zhe; Ialnazov, Dimiter S. (Frontiers in Sustainability, 2022)
In this paper we study the Solar Energy for Poverty Alleviation Program (SEPAP) in China, which aims to increase the 3,000 Yuan annually for poor people by installing solar panels. SEPAP was initially launched in 2014 and officially ended in 2020 when President Xi announced that absolute poverty was eliminated in China. During the six years, China built and put into operation 26.49 million kilowatts of solar PV systems, benefiting 1,472 counties, 138,091 villages, and 4.18 million poor households. We propose a sustainable assessment framework and apply the Analytic hierarchy process (AHP) and Fuzzy comprehensive evaluation method (FCEM) to evaluate individual-level SEPAP in Jinzhai County, China, based on the findings of 80 semi-structured interviews with professionals and poor households. When examining SEPAP sustainability, we discover that the economic dimension is the most crucial one, with income, employment, training for the poor, and solar panel quality being the most weighted sub-indicators. In 2021, SEPAP could increase by roughly 2700 Yuan for poor households, which is 90% achieved the governmental goals. We obtain a "Medium-high" outcome for the individual-level SEPAP. We provide two policy recommendations for maintenance work that will help the poor maintain a steady income.